2003
DOI: 10.1161/01.hyp.0000093383.18302.a7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the (mRen-2)27 Rat Is Not Explained by Enhanced Kinetics of Transgenic Ren-2 Renin

Abstract: Abstract-Enhanced efficiency of the reaction between transgenic Ren-2 mouse renin and endogenous rat angiotensinogen has been suggested as 1 mechanism that contributes to the accelerated hypertension and increased tissue angiotensin of the (mRen-2)27 transgenic rat. This was tested in a study conducted at pH 7.4 in vitro that compared the kinetic constants of purified mouse Ren-2 and rat renin (each at 100, 75, 50, and 25 pmol/L) reacting with physiologic concentrations of rat angiotensinogen (0 to 4 mol/L). U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Moreover, we and others [8][9][10][11] found that plasma and kidney ANG II levels are not elevated in TGR during the developmental and early phases of hypertension. Finally, it has been reported recently that hypertension in TGR is not related to renin kinetics [12]. Taken together, these results demonstrate that the development of hypertension in TGR could not simply be explained on the basis of increased production of ANG II with subsequent overactivation of AT 1 receptors and, therefore, other mechanisms had to be considered.…”
Section: Introductionmentioning
confidence: 54%
“…Moreover, we and others [8][9][10][11] found that plasma and kidney ANG II levels are not elevated in TGR during the developmental and early phases of hypertension. Finally, it has been reported recently that hypertension in TGR is not related to renin kinetics [12]. Taken together, these results demonstrate that the development of hypertension in TGR could not simply be explained on the basis of increased production of ANG II with subsequent overactivation of AT 1 receptors and, therefore, other mechanisms had to be considered.…”
Section: Introductionmentioning
confidence: 54%
“…This biochemically determined upper limit would help protect the body from excessive and deleterious Ang II concentrations caused by high Ang-N concentrations. A greater rise in BP has been described only for heterologous mouse renin acting on transgenic rat Ang-N causing abnormally accelerated reaction kinetics [14,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, submandibular renin does not enter the circulation in large quantities. Interestingly, Ren2 expression in the rat ([mRen2]27 rat) results in severe hypertension, most likely because mouse Ren2 renin reacts as well with rat angiotensinogen as rat renin does [45].…”
Section: Submandibular Glandmentioning
confidence: 99%